Psikologi PAK dalam Pendidikan Karakter untuk Mengembangkan Nilai-Nilai, Integritas, dan Kebajikan-kebajikan Penting - Rina Poibe Panjaitan (STT HKBP Pematangsiantar, 2024)
This article discusses the pivotal role of character as a moral self-transformation in individual development, focusing on character education in schools. The process of moral self-transformation involves reflecting on moral values, holistic development, and cultivating positive habits. The article also examines the role of Psychology in Christian Religion Education in supporting character formation with a profound scientific perspective. The research methodology applied is a literature review, investigating various literary sources related to character education. In conclusion, character education emerges as a strategic key in navigating the complexities of the modern world and constructing a fair and moral society.